Tumor-derived extracellular vesicles: reliable tools for Cancer diagnosis and clinical applications - Rahbarghazi, Reza (Cell Commun Signal, 2019)
BACKGROUND: Studies have recently revealed that almost every type of cells including tumor cells abundantly release small vesicles known as extracellular vesicles (EVs) into the extracellular milieu. EVs carry a repertoire of biological molecules including nucleic acids, proteins, lipids, and carbohydrates and transport their cargo between cells in the vicinity as well as distantly located cells and hence act as messengers of intercellular communication. In this review, we aimed to discuss the tumor-derived exosome biology and the pivotal roles of exosomes in cancer diagnosis and treatment. METHODS: In the present review study, the authors studied several articles over the past two decades published on the kinetics of EVs in tumor environment as well as on the application of these vesicles in cancer diagnosis and therapy. RESULTS: A growing body of evidence indicates that nucleic acids such as microRNAs (miRNAs) transferring by EVs participate to create a conducive tumor environment. As EV-associated miRNAs are tissue-specific and present in most biological fluids, they hold great potential for clinical application in cancer early diagnosis, prognosis, and treatment response. Furthermore, exosomes can serve as drug delivery vehicles transferring miRNAs as well as therapeutic agents to target cells. These nano-vesicles exhibit ideal properties in comparison with the synthetic carriers that attracted scientist’s attention in the field of nanotechnology medicine. Scientists have employed different strategies to build exosomes-based drug delivery system. In general, two methods (direct engineering and indirect engineering) are being utilized to produce artificial exosomes. Para-clinical data have confirmed the beneficial effects of engineering exosomes in cancer therapy. CONCLUSION: Exosomal miRNAs hold great promise for clinical application in early diagnosis and treatment of cancers. In addition, in spite of enthusiastic results obtained by engineered exosomes, however, there is an increasing concern over the use of optimal methods for engineering exosomes and the safety of engineered exosomes in clinical trials is still unclear.